Mistaken identity : two families, one survivor, unwavering hope - Van Ryn, Don (New York : Howard Books, 2008)
Meet Laura Van Ryn and Whitney Cerak: one buried under the wrong name, one in a coma and being cared for by the wrong family. This shocking case of mistaken identity stunned the country and made national news. Would it destroy a family? Shatter their faith? Push two families into bitterness, resentment, and guilt? Two traumatized families describe their ordeal and explore the bond sustaining and uniting them as they deal with their bizarre reversal of life lost and life found. And Whitney Cerak, the sole surviving student, comes to terms with her new identity, forever altered, yet on the brink of new beginnings. This book weaves a complex tale of honesty, vulnerability, loss, hope, faith, and love in the face of one of the strangest twists of circumstances imaginable.-- From publisher description
Keywords: Van Ryn, Don -- Family; Cerak, Newell -- Family; Traffic accidents -- United States -- Psychological aspects -- Case studies; Mistaken identity -- United States -- Case studies; Traffic accident victims -- United States -- Identification -- Case studies; Traffic accident victims -- Rehabilitation -- United States -- Case studies; Daughters -- Biography; Spiritual biography -- United States; Fort Wayne (Ind.) -- Biography; Gaylord (Mich.) -- Biography